The Impact of Digital Transformation in Food and Beverage Sector SMES: The Role of Leadership and Organizational Agility - Sidabutar Apriliene; Siswanto Joko (E3S Web of Conferences, 2024)
The pandemic caused a negative growth effect on the Indonesian economy in 2020 at 2.07 percent. Another effect is seen in the lifestyle shifted in society towards digitalization, which is increasingly evident over time. SMEs as one of the foundations of the Indonesian economy with 60.5% contribution to GDP in 2022 need to make adjustments to changes. The shift towards digital in business makes SMEs need to respond quickly to be able to meet customer needs. Changes in the SMEs environment makes leaders having to ensure that the SMEs they lead develop in the right direction. This study aims to determine the effect of digital transformation on food and beverage SMEs by considering the variables of leadership, organizational agility, and its effect on SMEs performance. The method used is a quantitative descriptive method. The study results found that leadership and organizational agility have a positive relationship with digital transformation in SMEs. This research also found that digital transformation has a positive relationship with the performance of SMEs.